A gas-kinetic BGK solver for two-dimensional turbulent compressible flow - Ong, Jiunn Chit; Omar, Ashraf Ali; Asrar, Waqar; Ismail, Ahmad Faris (2008)
In this paper, a gas kinetic solver is developed for the Reynolds Average Navier-Stokes (RANS) equations in two-space dimensions. To our best knowledge, this is the first attempt to extend the application of the BGK (Bhatnagaar-Gross-Krook) scheme to solve RANS equations with a turbulence model using finite difference method. The convection flux terms which appear on the left hand side of the RANS equations are discretized by a semi-discrete finite difference method. Then, the resulting inviscid flux functions are approximated by gas-kinetic BGK scheme which is based on the BGK model of the approximate collisional Boltzmann equation. The cell interface values required by the inviscid flux functions are reconstructed to higher-order spatial accuracy via the MUSCL (Monotone Upstream-Centered Schemes for Conservation Laws) variable interpolation method coupled with a minmod limiter. As for the diffusion flux terms, they are discretized by a second-order central difference scheme. To account for the turbulence effect, a combined k-ε / k-ω SST (Shear-Stress Transport) two-equation turbulence model is used in the solver. An explicit-type time integration method known as the modified fourth-order Runge-Kutta method is used to compute steady-state solutions. The computed results for a supersonic flow past a flat plate where the transition is artificially triggered at 50% of plate length are presented in this paper. Validating the computed results against existing analytical solutions and also comparing them with results from other well-known numerical schemes show that a very good agreement is obtained.